Encyclopedia of molecular pharmacology - Offermanns, Stefan; Rosenthal, Walter (SpringerLink Bücher, 2008)
An essential text, this is a fully updated second edition of a classic, now in two volumes. It provides rapid access to information on molecular pharmacology for research scientists, clinicians and advanced students. With the A-Z format of over 2,000 entries, around 350 authors provide a complete reference to the area of molecular pharmacology. The book combines the knowledge of classic pharmacology with the more recent approach of the precise analysis of the molecular mechanisms by which drugs exert their effects. Short keyword entries define common acronyms, terms and phrases. In addition, detailed essays provide in-depth information on drugs, cellular processes, molecular targets, techniques, molecular mechanisms, and general principles